Impact of Vegetation Species on the Elimination of Total Nitrogen and Total Phosphorus by Bioretention System - Mohmad Sakarnor, Muhammad Nadzmi (Universiti Teknologi PETRONAS, 2017)
Bioretention system or also widely-known as rain gardens are globally being implemented especially in the developed countries. It is classified as one of the stormwater Best Management Practices (BMPs) which the main goal is to wellmanaged the stormwater runoff at a relatively acceptable cost. The functionality of bioretention system is to reduce the highly exceeding nutrients and pollutants which may cause various harmful effects towards the environment and health. Conventionally, bioretention system is made up of only engineered soil media. Anyhow, innovatively by time, researchers have found additional materials as an addon to enhance the nutrient and pollutant removal performance, which also is being implemented in this study. Few of it are the integration of compost in small percentage into the engineered soil media. On the other hand, the plantation of various landscape plants also has significant impact on the elimination of nutrients besides having an aesthetic and beautiful scenic landscapes look.